Redox-Regulation of α-Globin in Vascular Physiology - Laurent Kiger; Julia Keith; Abdullah Freiwan; Alfonso G. Fernandez; Heather Tillman; Brant E. Isakson; Mitchell J. Weiss; Christophe Lechauve (MDPI AG, 2022)
Interest in the structure, function, and evolutionary relations of circulating and intracellular globins dates back more than 60 years to the first determination of the three-dimensional structure of these proteins. Non-erythrocytic globins have been implicated in circulatory control through reactions that couple nitric oxide (NO) signaling with cellular oxygen availability and redox status. Small artery endothelial cells (ECs) express free α-globin, which causes vasoconstriction by degrading NO. This reaction converts reduced (Fe2+) α-globin to the oxidized (Fe3+) form, which is unstable, cytotoxic, and unable to degrade NO. Therefore, (Fe3+) α-globin must be stabilized and recycled to (Fe2+) α-globin to reinitiate the catalytic cycle. The molecular chaperone α-hemoglobin-stabilizing protein (AHSP) binds (Fe3+) α-globin to inhibit its degradation and facilitate its reduction. The mechanisms that reduce (Fe3+) α-globin in ECs are unknown, although endothelial nitric oxide synthase (eNOS) and cytochrome b5 reductase (CyB5R3) with cytochrome b5 type A (CyB5a) can reduce (Fe3+) α-globin in solution. Here, we examine the expression and cellular localization of eNOS, CyB5a, and CyB5R3 in mouse arterial ECs and show that α-globin can be reduced by either of two independent redox systems, CyB5R3/CyB5a and eNOS. Together, our findings provide new insights into the regulation of blood vessel contractility.